THE INFLUENCE OF PROFESSIONAL DEVELOPMENT, ROLE OF THE INTERNAL AUDIT FUNCTION, EXPERIENCE OF UNDERSTANDING THE RISK BASED INTERNAL AUDIT WITH SELF EFFICACY AS A MODERATING VARIABLE ON THE INSPECTORATE OF SUMATERA UTARA PROVINCE - Widasari, Ira Puspita (International Journal of Public Budgeting, Accounting and Finance, 2018)
Risk Base Internal Audit (RBIA) is a methodology used by the internal audit function to provide confidance that risk appetite (an acceptable risk to the organization). This research aimed to know the influence of professional development, role of internal audit function, experience to the understanding of risk based internal audit at the Inspectorate of North Sumatera Province and to know the self efficacy in moderating the influence of professional development, role of internal audit function, experience to the understanding of risk based internal audit at the Inspectorate of North Sumatera utara. This type of research is causality research with the sampling technique used is census. There are 85 APIP as respondents. The data used is the primary data using the questionaire. Result of research indicate 1) professional development, and role of internal audit function have a significant positive effect on understanding of risk based internal audit, while experiace has positive effect insignificant to understanding of risk based internal audit. 2) self efficacy is not able to moderate the influence of professional development, role of internal audit function, and experience in the underatanding of risk based internal audit at the Inspectorate of North Sumatera Province.